Rozważania wokół wartości logicznych - Godycki-Ćwirko, Maciej (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1988)
The author formulates in this article a point of view, which is promptedby works dealing with the problem of logical values. There is analyzed a viewthat logical value of the sentence p is identical or at least connected with an answer to a question making it necessary to determine:The analysis is also focussed on four questions-problems:1. Can a question be always formulated?2. Does an answer always exist?3. Do conjunctions influence an answer in the case ofand how?4. Does only one answer exist?